The Substance View: A Critique (Part 2). (20th September 2012) - Lovering, Rob
ABSTRACT In my initial critique of the substance view, I raised reductio‐style objections to the substance view's conclusion that the standard human fetus has the same intrinsic value and moral standing as the standard adult human being, among others. In this follow‐up critique, I raise objections to some of the premises invoked in support of this conclusion. I begin by briefly presenting the substance view as well as its defense. (For a more thorough presentation, see the first part of my critique.) I then raise objections to three claims involved in the substance view's defense: the claim that the standard human fetus's intrinsic value and moral standing is a function of its potentiality; the claim that the standard human fetus's intrinsic value and moral standing is a function of its essential properties; and the claim that it is the possession of the basic potential for rational moral agency that best accounts for the wrongness of killing the standard human fetus, among others.